2012
DOI: 10.1186/2191-1991-2-22
|View full text |Cite
|
Sign up to set email alerts
|

The effects of public and private health care expenditure on health status in sub-Saharan Africa: new evidence from panel data analysis

Abstract: BackgroundHealth care expenditure has been low over the years in developing regions of the world. A majority of countries in these regions, especially sub-Saharan Africa (SSA), rely on donor grants and loans to finance health care. Such expenditures are not only unsustainable but also inadequate considering the enormous health care burden in the region. The objectives of this study are to determine the effect of health care expenditure on population health status and to examine the effect by public and private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
215
5
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(265 citation statements)
references
References 16 publications
33
215
5
12
Order By: Relevance
“…17 In a similar study covering 44 countries in Sub Saharan Africa the results showed that both public and private health care spending showed strong positive association with health status even though public health care spending had relatively higher impact. 18 In the present study too countries that had a relatively high percent of government spending on health had better infant mortality indicators, on the other hand countries which had a high proportion of private spending on health did not necessarily have a lower IMR. Governmental health spending on health in terms of per capita was the most important determinant of IMR.…”
Section: Resultscontrasting
confidence: 45%
“…17 In a similar study covering 44 countries in Sub Saharan Africa the results showed that both public and private health care spending showed strong positive association with health status even though public health care spending had relatively higher impact. 18 In the present study too countries that had a relatively high percent of government spending on health had better infant mortality indicators, on the other hand countries which had a high proportion of private spending on health did not necessarily have a lower IMR. Governmental health spending on health in terms of per capita was the most important determinant of IMR.…”
Section: Resultscontrasting
confidence: 45%
“…Novignon, Olakojo, and Nonvignon (2012) study 44 SSA countries using fixed effects estimations for the period 1995-2010, and find that health expenditure significantly improves life expectancy, and reduces death and infant mortality rates. They find that both private and public healthcare spending showed a strong positive association with health status, with public healthcare spending having the higher effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A same study in Nigeria also showed that public health expenditure has a negative effect on infant mortality and under-5 mortalities [22]. Novignon et al [7] in a study which was conducted in 2012, assessed the effects of public and private health care expenditure on health status in the SubSaharan Africa region. Their study also showed that both the public and private health spending can positively lead to a better health status through improving life expectancy at birth, reducing death and infant mortality rate but public health care spending had relatively higher impact.…”
Section: Discussionmentioning
confidence: 99%
“…These gains can be attributed to a number of factors, including better education, nutrition, sanitation, housing as well as greater access to health services [4,5]. Several studies have confirmed that there is a positive relationship between life expectancy at birth and health expenditure per capita worldwide [6][7][8]. A recent study by Joumard [9] in 2010 showed that an increase of total health spending is the possible reason for at least 40% of improvements in life expectancy since 1990.…”
Section: Introductionmentioning
confidence: 98%